Plasma density measurement by means of self-modulation of long electron bunches. (7th March 2019) - Loisch, G; Asova, G; Boonpornprasert, P; Chen, Y; Good, J; Gross, M; Huck, H; Kalantaryan, D; Krasilnikov, M; Lishilin, O; Melkumyan, D; Oppelt, A; et al.
Abstract: We present a new method to determine the electron density of a plasma by measuring the periodicity of modulations introduced to the longitudinal phase space of a relativistic particle bunch by the interaction with the plasma via the self-modulation instability. As the modulation is solely depending on the plasma density and the beam parameters, this method allows to determine the time-resolved density of a plasma at the position of beam passage, which is confirmed in particle-in-cell simulations. Densities in the range of 3.6 × 10 12 cm −3 – 7.2 × 10 15 cm −3 have been measured and the measurement accuracy is confirmed by comparison to spectroscopic plasma density measurements.